TOWARD AN INTERDISCIPLINARY FRAMEWORK FOR EDUCATIONAL INCLUSIVITY - DeLuca, Christopher (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
This purpose of this paper is to provide a theoretical foundation for inclusion in Canadian schools for this Special Issue on Inclusive Education. In response to the need for an interdisciplinary framework, this paper uses an interpretive literature review methodology to construct a framework for educational inclusivity based on four disciplinary perspectives: (a) special education and disability studies, (b) multiculturalism and anti-racist education, (c) gender and women’s education, and (b) queer studies. The constructed framework elucidates four conceptions of inclusivity––normative, integrative, dialogical, and transgressive––positioned on a continuum with each conception representing a different approach to inclusion. Unlike previous models, this framework is not anchored to any one marginalized group; rather, it is intended to represent multiple forms of inclusivity to edify historical, existing, and idealistic educational practices and structures for all forms of difference.